Investigating the application of Narrative Exposure Therapy (NET) to reduce symptoms of traumatic stress in cancer patients not in active treatment: a naturalistic single case study series - D'Errico, Danila (2023)
Objective: This study aimed to evaluate the feasibility, acceptability, and effectiveness of Narrative Exposure Therapy (NET) in reducing symptoms of traumatic stress, anxiety and depression, and existential anxiety, and in improving quality of life and promoting post-traumatic growth in cancer patients not in active treatment.